Pre-dilation and Post-dilation in Transcatheter Aortic Valve Replacement: Indications, Benefits and Risks - Angela McInerney; Rafael Vera-Urquiza; Gabriela Tirado-Conte; Luis Marroquin; Pilar Jimenez-Quevedo; Iván Nuñez-Gil; Eduardo Pozo; Nieves Gonzalo; Jose Alberto de Agustín; Javier Escaned; Antonio Fernández-Ortiz; Carlos Macaya; et al. (Interventional Cardiology: Reviews, Research, Resources, 2021)
Transcatheter aortic valve replacement (TAVR) is an established treatment for patients with symptomatic severe aortic stenosis. In recent years, an emphasis has been placed on simplification of the procedure. Balloon predilation was initially considered a mandatory step to cross and prepare the stenotic aortic valve, but several studies demonstrated the feasibility of performing TAVR without balloon valvuloplasty. Balloon postdilation of the implanted valve is sometimes required to optimise results, although many patients do not require this step. Contemporary consensus advocates an individualised approach to TAVR procedures and so balloon pre- and post-dilation are performed selectively. This review aims to outline the advantages and disadvantages of balloon pre- and post-dilation and to identify the scenarios in which they are required during TAVR procedures.